Analisis Peran Dosen Mengatasi Kesulitan Mahasiswa dalam Active Speaking dengan Menggunakan CLT pada Mata Kuliah Bahasa Inggris di Prodi PAI IAIDU Asahan: Analysis of the Role of Lecturers in Overcoming Students' Difficulties in Active Speaking by Using CLT in English Courses at the Islamic Education Study Program IAIDU Asahan - Marpaung, Agus Salim; Pulungan, Putri Suaidah (Anterior Jurnal, 2025)
This research aims to analyze the role of lecturers in overcoming students' difficulties in active speaking using the Communicative Language Teaching (CLT) approach in English courses in the IAIDU Asahan Islamic Religious Education (PAI) Study Program. English speaking skills are one of the important competencies that students must master, especially in this era of globalization. This research uses a qualitative descriptive method by collecting data through observation, interviews, and document analysis. The research subjects were lecturers and students at the PAI IAIDU Asahan Study Program. The research results show that the role of lecturers is very significant in helping students overcome their difficulties in active speaking. The application of CLT has proven to be effective in improving students' active speaking skills, because this approach emphasizes the use of language in real communication contexts, provides interactive exercises, and creates a supportive learning environment. This research also found that the lecturer's role is not only as a facilitator but also as a motivator and guide who provides constructive feedback and encouragement for students to continue practicing speaking in English. Based on these findings, it is hoped that lecturers can continue to develop adaptive and innovative teaching methods to help students overcome their challenges in active speaking.